Reflective experience report of supervised internship: prototyping didactic proposal to use podcast as an educational tool (Olhar de Professor, 2024)
This work is an experience report developed within the scope of the supervised internship of the Graduate Program in Education and Science Teaching in the Amazon. Its objective was to assess whether the adoption of podcasts as a knowledge application strategy assists in the teaching and learning process of Basic Education students. The activities were conducted through a teaching sequence, supported by Paulo Freire’s pedagogy and structured in the Three Pedagogical Moments format. First-year high school students were challenged to participate in the production of an educational podcast on Water Pollution and Contamination. Three episodes were produced. Finally, an individual questionnaire was administered, focusing on understanding the participants' perception of the educational potential of podcast production. The data analysis revealed a widespread understanding of the aspects that enhance podcasts as an educational tool, as well as the democratization of technology access, thus allowing for the sharing of knowledge and experiences.
Keywords: Knowledge production.; Digital technology.; Learner.